Screening of Polyphenolic Compounds in Echinochloa crusgalli Roxb Extracts by Various Analytical Techniques - Sathis Kumar, D.; Banji, David; Harani, A.; Tirupathi Rao, A.; Nageswar Rao, S.; Pavan Kumar, Ch.; Santhi Krupa, D. (Asian Journal of Chemistry, 2013)
In the present study, the phenolic content of the selected extracts of Echinochloa crusgalli Roxb plants were determined with chromatographic techniques like thin layer chromatography, high performance thin layer chromatography and high performance liquid chromatography while the total phenol was determined by UV method. All the results of analytical methods were compared with standard phenolic compounds. The methanol macerated extract contained maximum total phenolic content (0.719 ± 0.67 mg GAE/g) than other extract by soxhlation. Eleven compounds identified by chromatographic techniques in the plant. The dominant phenolic compounds representing the main groups in Echinochloa crusgalli are flavonoids and phenol carboxylic acids. From LCMSMS results suggested that the myricetin, quercetin, artemisinin, cyanidin, kaempferol, luteolin, bilobol and its derivatives may be present in methanolic extracts of Echinochloa crusgalli Roxb. It may assign a new potential role of Echinochloa crusgalli Roxb extract in human health care.